2002
DOI: 10.1136/thorax.57.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation, basement membrane thickening and bronchial hyperresponsiveness in asthma

Abstract: Background: There are few data in asthma relating airway physiology, inflammation and remodelling and the relative effects of inhaled corticosteroid (ICS) treatment on these parameters. A study of the relationships between spirometric indices, airway inflammation, airway remodelling, and bronchial hyperreactivity (BHR) before and after treatment with high dose inhaled fluticasone propionate (FP 750 µg bd) was performed in a group of patients with relatively mild but symptomatic asthma. Methods: A double blind,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
310
4
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(344 citation statements)
references
References 37 publications
17
310
4
13
Order By: Relevance
“…13 A considerable overlap between asthmatic and healthy subjects was indicated to support the view that this aspect of airway remodeling does not necessarily discriminate individual asthmatic subjects from healthy subjects, whereas airway remodeling is generally present in asthmatic subjects as a group, which may be related to physiological change and can be positively affected by long-term therapy with inhaled corticosteroids. 25,33 A major limitation of our study is the small sample size, which limits the generalizability of our findings by making them arguable in terms of statistical power, whereas the study inclusion criteria are in accordance with the good control of external effects, and international guidelines were well followed. Hence, our study has merit and is relevant from a clinical point of view as it suggests that even mild intermittent asthma may induce structural changes in the small airways.…”
Section: Discussionmentioning
confidence: 99%
“…13 A considerable overlap between asthmatic and healthy subjects was indicated to support the view that this aspect of airway remodeling does not necessarily discriminate individual asthmatic subjects from healthy subjects, whereas airway remodeling is generally present in asthmatic subjects as a group, which may be related to physiological change and can be positively affected by long-term therapy with inhaled corticosteroids. 25,33 A major limitation of our study is the small sample size, which limits the generalizability of our findings by making them arguable in terms of statistical power, whereas the study inclusion criteria are in accordance with the good control of external effects, and international guidelines were well followed. Hence, our study has merit and is relevant from a clinical point of view as it suggests that even mild intermittent asthma may induce structural changes in the small airways.…”
Section: Discussionmentioning
confidence: 99%
“…Si on estime que ces changements précèdent le diagnostic clinique, les interventions thérapeutiques de type anti-inflammatoire n'interviendront peut-être jamais assez tôt pour être efficaces [2]. Les résultats des traitements par des fortes doses de CSI sont contradictoires : pour certains, elles entraînent une diminution de l'hyperactivité bronchique attribuée pour les deux tiers à une diminution du remodelage, et un tiers à la diminution de l'inflammation [32]. En revanche, d'autres études n'ont pas permis de conclure à un effet des CSI sur le remodelage bronchique [33].…”
Section: Les Thérapeutiques Actuelles Et Futuresunclassified
“…Although not studied in the GOAL study, a number of studies have shown that long-term treatment with ICS leads to a reduction in airway inflammation and hyper-responsiveness, and a reversal in airway remodelling. [11][12][13] In the study by Ward et al, although a reduction in inflammatory cell counts was seen after three months of treatment with fluticasone propionate, improvements in airway remodelling were not seen until 12 months of treatment. 11 The effects of ICS therapy in airway remodelling are a source of controversy and this issue requires further research.…”
mentioning
confidence: 99%
“…[11][12][13] In the study by Ward et al, although a reduction in inflammatory cell counts was seen after three months of treatment with fluticasone propionate, improvements in airway remodelling were not seen until 12 months of treatment. 11 The effects of ICS therapy in airway remodelling are a source of controversy and this issue requires further research.The GOAL study used a stable dosing treatment strategy, following an initial titration period. Further support for a longer-term stable dosing approach has been suggested by the CONCEPT study, in which patients who stepped-up their treatment and were stable initially on salmeterol/fluticasone propionate (50/250 mcg twice daily) had substantially better long-term outcomes than patients randomised to adjusted dosing with formoterol/budesonide (6/200 mcg), which allowed patients to reduce their treatment to once daily.…”
mentioning
confidence: 99%